Approach in ordering child: rehabilitation in Tunas Bakti School / Mohd Izhanudin Alias, Khairy Ezany Bakhtiar and Siti Royani Sabri - Alias, Mohd Izhanudin; Bakhtiar Nor, Khairy Ezany; Sabri, Siti Royani (2007)
This paper is set out to review on the ordering process of child in tunas Bakti School and to review on its effectiveness. The purpose of this research is to evaluate the existing law, either it is sufficient or if it is not, what are the provision on the Child Act that need more clarifications and amend to give more power to the existing body which have the responsibility to rehabilitate the children in the approved school as to avoid mishandling and ultravires act. Upon research and making this paper, it is transpired that, the aftercare programme, under section 70 of the Child Act 2001, need more interpretation and to be amended for the benefit of the child, and other part of the Child Act itself need to be reviewed again, as to maintain the definition of the rehabilitation and yet we suggesting standardization of the approve school in management and in legal aspect as to limit the discretionary element in rehabilitation of child as that element may tainted with ultravires act and the child shall open to mishandling and attack.